Personnel Policy Conceptualization in the Context of the Scientific Research Development in the Sphere of Criminal Law - Hasanovich Rakhmetov, Talgat; Petrovna Shchukina, Nina; Pavlovna Gagarinskaya, Galina; Vladimirovna Muller, Elena; Vladimirovna Shmidt, Arina (International Journal of Criminology and Sociology, 2022)
the current stage of criminal law development is characterized by changing requirements for the personnel skills due to their increasing significance in jurisprudence as a unified system. Therefore, there is a necessity for high-quality and relevant scientific research on personnel management in the area of criminal law. The purpose of the present work is to monitor and objectively assess the features of scientific research on personnel policy that contribute to the development of criminal law as a subject area in Russia. The authors apply the content analysis to study 343 research bulletins of the “Main Results of Scientific Research” from 2006 to 2018 focusing on the structure, design, scientific results, thematic area, relevance and methodology, which reveal the problems of transformation and development of the personnel policy concepts in criminal law. According to the interpretation method, it is substantiated that the scientific priority of research corresponds to the modern trends in the development of the personnel management system in the Russian jurisprudence. In addition, it is characterized by structural and methodological defectiveness, which leads to a decrease in the scientific character of the research’s results obtained. Consequently, their implementation in penitentiary institutions is impossible. It is proved that the implementation of common requirements for the methodology of scientific research on personnel policy based on creativity, validity, science and unambiguity improves the efficiency of scientific research and forms the basis for new scientific developments. The obtained results are of an applied nature and can be useful for the development of the general requirements for scientific publications in research bulletins of the “Main Results of Scientific Research, and also in other scientific research publications on personnel management in criminal law.